Redução do "craving" ao uso de crack-cocaína produzida pela modulação do córtex pré-frontal dorsolateral por estimulação cerebral transcraniana por corrente contínua de baixa intensidade - Batista, Edson Kruger (2015)
Transcranial Direct Current Stimulation (tDCS) over dorsolateral prefrontal cortex (dlPFC) has been shown to be clinically useful in the treatment of drug addiction. This was a double-blind randomized clinical trial aiming to examine the modulatory effects of repetitive bilateral tDCS over dlPFC (left cathodal/right anodal) on crackcocaine addiction, having craving as the primary outcome and other clinical measurements, including global cognitive status, frontal function, depressive and anxiety symtoms, and quality of life, as secondary outcomes. 17 male crack-cocaine users (mean age 30.4 ± 9.8 SD) were randomized to receive five sessions of active tDCS (2 mA, 35 cm2 , for 20 minutes), every other day, and 19 males (mean age 30.3 ± 8.4 SD) to receive sham-tDCS (placebo), as a control group. Craving scores significantly reduced the tDCS group after treatment when compared to sham-tDCS (p = 0.028) and to baseline values (p = 0.003), and decreased linearly over the 4- weeks (before, during and after treatment) in the tDCS group only (p = 0.047). Changes of anxiety scores towards increasing in the sham-tDCS and decreasing in the tDCS group (p = 0.03), and of the overall perception of quality of life (p = 0.031) and of health (p = 0.048) towards decreasing in the sham-tDCS group and increasing in the tDCS group, differed significantly between groups. Repetitive bilateral tDCS over the dlPFC reduced craving to crack-cocaine use, decreased anxiety and improved quality of life. We hypothesize that repetitive tDCS effects may be associated with increased pre-frontal processing and regulation of craving behavior.